2015
DOI: 10.1179/1607845415y.0000000038
|View full text |Cite
|
Sign up to set email alerts
|

The association of cytokine genes polymorphisms and susceptibility to aplastic anemia in Egyptian patients

Abstract: IFN-γ +874 A/T gene polymorphism is associated with the etiology of AA in Egyptian patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(45 reference statements)
0
5
1
Order By: Relevance
“…. TNF-α-308 positively correlated with AA in our population; this result is not in agreement with earlier findings available on the subject [22]. This inconsistency might be due to the smaller sample size, selection criteria, ethnicity, and geographical variation of study subjects.…”
Section: Plasma Concentrations Of Tnf-α-308 and Ifn-γ-874 In Patientscontrasting
confidence: 93%
“…. TNF-α-308 positively correlated with AA in our population; this result is not in agreement with earlier findings available on the subject [22]. This inconsistency might be due to the smaller sample size, selection criteria, ethnicity, and geographical variation of study subjects.…”
Section: Plasma Concentrations Of Tnf-α-308 and Ifn-γ-874 In Patientscontrasting
confidence: 93%
“…No additional studies were found by manual search. Finally, five articles were included in this meta-analysis [10][11][12][13]16].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All these studies detected the polymorphisms of IFN-γ by PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism), PCR-SSP (polymerase chain reaction-sequence-specific primer) or ARMS-PCR (amplification refractory mutation system-polymerase chain reaction), except one study did not describe the detection method [13]. The polymorphisms of IFN-γ of the controls in each included study met the Hardy-Weinberg equilibrium, except El Mahgoub IR 2014 [11] and Zayed RA 2015 [16]. In addition, based on the NOS scores, no low-quality studies were included in this meta-analysis (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…gene polymorphisms were explored to estimate the correlation with genetic predisposition to aplastic anemia; nonetheless, few explicit contributors have been identified. [25][26][27] Among the polymorphic sites identified, HLA-DPB1, IFNγ + 874 A/T, and TNFα-308 G/A were proved to contribute to the susceptibility of aplastic anemia. 25,26 The IL-27 gene, located in chromosome 16p11, plays important role in regulating polarization of T cells.…”
Section: Discussionmentioning
confidence: 98%